A method for preparing MXene / TPU conductive fibers
Through wet spinning and impregnation coating processes, the functionally modified PDA@MXene/TPU elastic fiber electrode solves the problems of uneven dispersion of MXene and the limitations of large-scale production, achieves high tensile properties, good conductivity and environmental stability, and expands the potential of fibers in the field of multifunctional applications.
Patent Information
- Application Number
- CN202310057833.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-01-16
AI Technical Summary
The existing conductive fiber preparation methods rely on simple mechanical mixing and complex post-treatment processes, resulting in uneven dispersion of MXene nanosheets and limited production on a large scale, affecting the mechanical characteristics, electrical characteristics and comprehensive application potential of the fiber.
Using wet spinning technology and impregnation coating process, MXene nanosheets were modified through in-situ self-polymerization of dopamine hydrochloride, and PDA@MXene/TPU elastic fiber electrodes were prepared to achieve high tensile properties, good conductivity and environmental stability.
It realizes a dispersion system without electrical performance loss and uniform and stable, improves the adhesion of the interface between conductive nanomaterials and polymers and the conductive phase discontinuous structure, ensures that the fibers still have electrical conductivity under high tensile deformation, and expands the potential of fibers in the field of multifunctional applications.
Smart Images

Figure CN116024696B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing MXene / TPU conductive fiber, and belongs to the technical field of composite conductive fibers. Background Art
[0002] In recent years, with the growing demand for flexible wearable electronic devices, the application of lightweight, portable and wearable one-dimensional conductive fiber materials in the fields of energy collection and storage, smart sensing, smart interconnection, etc. has received extensive research attention. Compared with traditional rigid structural materials, fiber electrodes have excellent mechanical strength, flexibility and easy integration. They can be integrated with commercial fibers and fabrics into smart textiles through further weaving methods, and show good application prospects in the development of fiber-based high-performance energy storage devices, electromagnetic shielding, piezoelectric sensors and other flexible electronic devices. For example, smart fabrics woven from fiber electrode materials and friction materials can be used to realize functions such as mechanical energy collection and conversion, electronic device driving, and active biosensing. At present, the most widely used one-dimensional conductive fiber materials are mainly carbon-based materials, liquid metals, conductive polymers, etc. However, there are still many problems in its development: first, the fiber preparation process is complicated and the cost is high; second, how to achieve large-scale continuous production in the preparation process is a key technical problem that restricts the industrial development of one-dimensional conductive fibers; in addition, due to the inherent characteristics of inorganic fillers, the current conductive fibers have low mechanical strength and poor flexibility, which cannot guarantee practical application in the field of smart wearables; in particular, the balance between the conductivity and stretchability of conductive fibers largely limits the practical application of fiber electrodes. Therefore, exploring a high-elastic substrate combined with a functional high-conductive material to prepare a large-scale one-dimensional conductive fiber with a cable-like structure provides a feasible solution and approach to solve the above problems.
[0003] Thermoplastic polyurethane (TPU) is a type of block copolymer obtained by polycondensation of isocyanate and polyether or diol polyester. It is a thermoplastic elastomer with good spinnability. In the preparation of flexible electronic devices, by introducing an appropriate amount of thermoplastic polyurethane material into the system, the material can be given excellent properties of high mechanical strength, flexibility and wear resistance, expanding its application in the fields of smart wearable fibers and smart fabrics. At present, thermoplastic polyurethane is prepared by blending fiber materials with many conductive materials, so that it not only has excellent mechanical properties, but also has excellent conductivity to meet actual use needs. The TPU fiber composite material prepared by wet spinning not only has high elastic recovery characteristics (up to 600% or more), but also has the ability of large-scale production, and has important application value in industrial production. In this scheme, TPU is used as the substrate. The purpose is to utilize TPU with excellent physical and chemical properties, especially good mechanical strength and flexibility. Through the wet spinning and drawing process, the mechanical and other related properties of the composite fiber electrode material are improved and further strengthened, and finally the practical application ability of the composite fiber electrode material in the fields of smart textiles is expanded.
[0004] Ti3C2T x MXene is a member of two-dimensional transition metal carbides / carbonitrides, and its chemical formula is M n+ 1X n T x (where M is an early transition metal, X is carbon or nitrogen, T xRepresenting active terminal groups, such as -O, -OH, -F, etc.) because of its metallic electrical properties, typical layered structure, surface characteristics and unique hydrophilicity make it an ideal unit for constructing structural and functional integrated fiber electrode composite materials, and it has shown excellent application prospects in many fields such as biosensing, energy storage, optoelectronics, and electromagnetic shielding. In addition, MXene is endowed with a large number of surface groups during hydrofluoric acid etching, which makes it exhibit good dispersibility in water and can be processed into fibers or fabrics through different processes such as spinning, coating and printing. These characteristics and easy processing have made breakthroughs in the research of MXene-based functional fibers and smart textiles. However, the instability of MXene in aqueous solution or air makes it extremely easy to oxidize and transform into titanium dioxide and amorphous carbon. The oxidation-sensitive properties of MXene weaken the many excellent properties of MXene, including surface hydrophilicity and metal conductivity, which greatly limits the practical application of MXene. In addition, MXene-based fiber electrodes will produce irreversible cracks between conductive materials when they are stretched, which greatly limits the application of fiber electrode materials. In response to the above problems, some researchers have been prompted to modify the functions of MXene to improve its colloidal stability and uniformity. However, current preparation methods mainly rely on simple mechanical mixing and complex post-processing processes, which may lead to uneven dispersion of MXene nanosheets and limitations in large-scale production, thus affecting the comprehensive performance of stretchable fiber electrodes. Summary of the invention
[0005]
Technical issues
[0006] Current conductive fiber preparation methods mainly rely on simple mechanical mixing and complex post-processing processes, which may lead to uneven dispersion of MXene nanosheets and limitations in large-scale production, thus affecting the mechanical properties, electrical properties and comprehensive application potential of stretchable fiber electrodes.
[0007]
Technical solution
[0008] The purpose of the present invention is to overcome the shortcomings of the prior art, solve the problem of electrical properties of elastic fiber electrodes under large tensile deformation and interface regulation of inorganic MXene and organic polymers, and prepare large-scale PDA@MXene / TPU elastic fiber electrodes with ultra-high stretchability, good conductivity and environmental stability through a simple and efficient wet spinning technology and dip coating process, and weave them into smart fabrics with commercial yarns, thereby providing a smart fiber, fabric and preparation method thereof that can simultaneously realize energy conversion and biosensing. The present invention utilizes dopamine hydrochloride to functionalize MXene nanosheets by in-situ self-polymerization to prepare a composite conductive ink (PDA@MXene), thereby obtaining a uniform and stable dispersion system without electrical performance loss, and at the same time, effectively improving its adhesion to the fiber matrix interface and the discontinuous structure of the polymer interface conductive phase, thereby better integrating the respective advantages of conductive nanomaterials and polymer elastomers to construct a large-scale preparation of fiber electrode materials, so that the fibers still have conductivity under high tensile deformation, obtaining a high-stretch, weavable fiber system, and giving it new multifunctional applications, thereby expanding the application of stretchable fiber electrode materials in the fields of friction nanogenerators, energy conversion, biosensors, wearable smart fabrics, etc.
[0009] The first object of the present invention is to provide a method for preparing MXene / TPU conductive fibers, wherein MXene is used as a conductive material and TPU is used as an elastic substrate, and MXene / TPU conductive fibers are obtained by wet spinning; the mass ratio of MXene to TPU is 20-60%.
[0010] In one embodiment of the present invention, the wet spinning process is:
[0011] Step 1, preparation of MXene / TPU composite solution: using lithium fluoride / hydrochloric acid (LiF / HCl) mixed solution etching combined with ultrasonic stripping to obtain a MXene colloid aqueous dispersion, dispersing the MXene powder obtained after freeze-drying in N'N-dimethylformamide, adding TPU particles thereto, and magnetically stirring at 25-60°C for 3-48h to obtain a MXene / TPU composite spinning solution;
[0012] Step 2, preparation of MXene / TPU composite fiber: the MXene / TPU spinning solution is injected into the coagulation bath by an injection pump, and the spinning fine stream is formed into fibers through a curing process and a drawing process, and the fibers are collected by a coagulation bath collecting device.
[0013] In one embodiment of the present invention, the wet spinning conditions are: ultrasonic power of 200-500 W, ultrasonic time of 30-60 min; temperature of 25-60° C., and magnetic stirring time of 3-48 h.
[0014] In one embodiment of the present invention, the coagulation bath in the wet spinning process is water, and the spinning solution extrusion rate is 1-6 mL min -1 , the drawing rate is 1-30rpm.
[0015] In one embodiment of the present invention, the MXene is an existing material, which refers to a two-dimensional transition metal carbide / carbonitride, which can be obtained by etching a precursor MAX phase; TPU refers to a thermoplastic polyurethane elastomer.
[0016] In one embodiment of the present invention, MXene is prepared according to the document M. Alhabeb, K. Maleski, B. Anasori, P. Lelyukh, L. Clark, S. Sin, Y. Gogotsi, Guidelines for Synthesis and Processing of Two-Dimensional Titanium Carbide (Ti3C2Tx MXene), Chemistry of Materials 29 (18) (2017) 7633-7644.
[0017] The second object of the present invention is to provide a MXene / TPU conductive fiber prepared by the above method.
[0018] The third object of the present invention is to provide a product containing MXene / TPU conductive fibers.
[0019] The fourth object of the present invention is to provide a PDA@MXene / TPU elastic fiber electrode, which comprises MXene / TPU conductive fiber and a PDA@MXene coating.
[0020] In one embodiment of the present invention, PDA@MXene refers to a functionalized modified MXene of in situ self-polymerized dopamine; the PDA@MXene is prepared with reference to LYYang, J.Cui, L.Zhang, XRXu, X.Chen, DPSun, AMoisture-Driven Actuator Based on Polydopamine-Modified MXene / BacterialCellulose Nanofiber Composite Film, Advanced Functional Materials 31(27)(2021).
[0021] A fifth object of the present invention is to provide a smart fabric, which comprises PDA@MXene / TPU elastic fiber electrodes and yarns, wherein the PDA@MXene / TPU elastic fiber electrodes and yarns are interwoven with each other.
[0022] The sixth object of the present invention is to provide an application of the above-mentioned PDA@MXene / TPU elastic fiber electrode in friction nanogenerators, self-powered sensors, wearable electronic devices, smart fibers / fabrics or flexible electrodes.
[0023] Beneficial effects of the present invention:
[0024] The technical solution of the present invention first designs and synthesizes Ti3C2T x MXene monomers, on this basis, surface functionalized PDA@MXene nanosheets were designed and synthesized, and then a conductivity superior to MXene (2614.8S cm -1 ) of PDA@MXene highly conductive ink (4335.1S cm -1 ); At the same time, the surface functionalized PDA@MXene conductive ink is due to Ti3C2T x The polar functional groups of MXene itself (such as -O, -F, -OH) and the adhesion properties of polydopamine can be coated on the surface of the elastic fiber electrode and firmly combined to form a uniformly distributed conductive network. The present invention not only solves the problems of existing MXene interface adhesion and environmental stability, but also gives the elastic fiber substrate the conductivity retention property under large tensile deformation.
[0025] The present invention cleverly combines the well-designed PDA@MXene functional conductive ink with the conductive polymer elastomer fiber without complicated processes. Through one-step large-scale wet spinning and a simple dip coating scheme, a simple large-scale flexible MXene-polymer elastomer wet spinning fiber electrode is developed. The fiber has both high mechanical properties (tensile strength of 2-6MPa, elongation at break of 150-900%) and excellent electrical properties (4.31S cm -1). The present invention adopts a high-speed centrifugal device and a coagulation bath system to complete the preparation of the conductive fiber. The process equipment is simple, and the price of thermoplastic polyurethane elastomer and other raw materials is relatively cheap. Therefore, the preparation method of the present invention also has the advantage of low cost. The present invention can realize the preparation of composite spinning solutions with a wide range and different doping mass ratios, and then control the viscosity, fiber morphology, mechanical and electrical properties of the spinning solution, thereby regulating the comprehensive performance of the composite fiber. Functionally modified PDA@MXene / TPU fiber electrodes are woven with polytetrafluoroethylene yarns into plain fabrics, which can be used in energy collection, energy storage, biosensing, artificial muscles, flexible wearable devices, and biomedicine. It is expected to play a new role in the development of unconstrained, self-driven sensing wearable smart fibers and smart fabrics.
[0026] Compared with other wet-spinning conductive fibers, the present invention has a simple experimental method, easy experimental conditions, and does not require high temperature and high pressure conditions. It can achieve large-scale preparation of continuous fibers with a high MXene content. At the same time, the process has extremely high production efficiency, and the output can reach 20g min -1 .
[0027] The MXene-polymer elastomer composite conductive fiber prepared by the present invention has a diameter of 200-400 μm, high mechanical strength and flexibility (2-6 MPa, 150-900%), excellent and stable electrical properties (4.31 S cm -1 ), which has the potential for large-scale industrial production. At the same time, the PDA@MXene functional coating on the surface of the composite fiber improves the fiber conductivity, which is beneficial to the maintenance of the electrical properties of the conductive fiber during high tensile deformation, and provides new insights for the development of fiber electrodes with excellent mechanical properties and electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the synthesis of PDA@MXene and the preparation of PDA@MXene / TPU fiber electrode of the present invention;
[0029] Figure 2 A physical picture showing the mechanical properties and large-scale preparation of the PDA@MXene / TPU elastic fiber electrode in the present invention;
[0030] Figure 3 The axial electron microscope image and EDSmapping element distribution diagram of the PDA@MXene / TPU wet-spun elastic fiber electrode in the present invention;
[0031] Figure 4 The Ti3C2T of Example 1 of the present invention x Transmission electron microscopy images of MXene and functionalized modified PDA@MXene;
[0032] Figure 5 The Ti3C2T of Example 1 of the present invention x X-ray diffraction patterns of MXene and functionalized modified PDA@MXene;
[0033] Figure 6 This is the X-ray photoelectron spectrum of the functionalized modified PDA@MXene of Example 1 of the present invention;
[0034] Figure 7 The stress-strain curves of the MXene / TPU wet-spun conductive elastic fiber electrodes of Examples 1-5 of the present invention;
[0035] Figure 8 The conductivity bar graphs of the MXene / TPU and PDA@MXene / TPU fiber electrodes of Examples 3 and 6 of the present invention;
[0036] Fig. 9 The conductivity change diagram of MXene / TPU and PDA@MXene / TPU fiber electrodes of Examples 3 and 6 of the present invention under large tensile deformation (0-100%);
[0037] Fig.10 This is a COMSOL potential simulation diagram of the PDA@MXene / TPU elastic fiber electrode used for the textile friction nanogenerator in Example 7 of the present invention;
[0038] Fig.11 The output characteristics (open circuit voltage and short circuit current) and cycle stability of the PDA@MXene / TPU elastic fiber electrode used for the textile friction nanogenerator in Example 7 of the present invention;
[0039] Fig.12 The PDA@MXene / TPU elastic fiber electrode in Example 7 of the present invention is used for the external load output power test of the textile friction nanogenerator;
[0040] Fig.13 This is a bending stability test of the PDA@MXene / TPU smart fabric in Example 7 of the present invention;
[0041] Fig.14 Demonstration of the PDA@MXene / TPU fabric-based friction nanogenerator in Example 7 of the present invention charging capacitors of different specifications and driving electronic watches;
[0042] Fig.15 The PDA@MXene / TPU fabric-based friction nanogenerator in Example 7 of the present invention is used for self-powered active biosensing of different parts of the human body. DETAILED DESCRIPTION
[0043] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0044] 1. Tensile performance test:
[0045] The MXene / TPU composite fibers were clamped in an electronic universal material testing machine with a spacing of 20 mm, and the breaking strength and breaking elongation of MXene / TPU composite fibers with different MXene contents were tested.
[0046] 2. Conductivity (σ) test:
[0047] The two ends of the MXene / TPU composite conductive wet-spun fiber with a length of 4 cm were clamped in the positive and negative electrodes of the electrochemical workstation. The linear voltammetric curve was Calculate the fiber resistance and then use the formula The fiber conductivity is calculated. Where U and I are the voltage and current across the MXene / TPU composite conductive wet-spun fiber, σ is the conductivity of the MXene / TPU composite conductive wet-spun fiber, and L, S and R are the length, cross-sectional area and resistance of the MXene / TPU composite conductive wet-spun fiber, respectively.
[0048] Example 1: A method for preparing MXene / TPU wet-spun conductive fibers
[0049] Step 1: Synthesis of Ti3C2T x MXene: Weigh 2.0g LiF powder and add it to 40mL 9M HCl. Stir magnetically at room temperature for 30min until the powder is completely dissolved. Slowly add 2.0g MAX Ti3AlC2 powder to the above solution and stir slowly at a constant temperature of 35°C for 48h. Wash the precipitate after centrifugation with deionized water several times until the pH of the supernatant is greater than 6. The centrifugation parameters for this process are 3500rpm 5min. Add 40mL of anhydrous ethanol to the precipitate washed to neutrality and shake well. Exfoliate the multilayer MXene by continuous ultrasound in an ice water bath at a power of 320W for 1h. After centrifugation at 10000rpm for 10min, continue to disperse the precipitate in deionized water; repeat the centrifugation several times and collect the supernatant, which is the single-layer MXene (such as attached Figure 1 The monolayer MXene dispersion was freeze-dried to obtain MXene powder.
[0050] Step 2: Preparation of MXene / TPU spinning solution: Weigh 200 mg of monolayer MXene powder and add it to 10 mL N,N-dimethylformamide (DMF). Ultrasonic treatment is performed at 320 W for 30 min to obtain a uniform monolayer MXene dispersion. Subsequently, 1.0 g of thermoplastic polyurethane elastomer particles is introduced and magnetic stirring is performed at room temperature for 12 h to obtain a binary spinning solution with a MXene content of 20 mg mL -1 MXene / TPU composite wet spinning solution.
[0051] Step 3: Preparation of MXene / TPU fiber: Take the MXene / TPU spinning solution prepared in step 2 for wet spinning. The wet spinning solution is injected into the coagulation bath 1 by the injection pump. Combined with the solvent-coagulation bath double diffusion relationship, continuous wet spinning, spinning fine stream solidification, drawing process and drying are carried out to obtain MXene / TPU (M2P) composite wet spinning fiber with controllable fiber diameter. The wet spinning parameters are as follows: the spinning solution flow rate of the syringe is 1.25mL min -1 The needle model is 16G, the collection roller collection speed is 15rpm, the coagulation bath is deionized water, and the average diameter of the fiber is 390μm.
[0052] Example 2: A method for preparing MXene / TPU wet-spun conductive fibers
[0053] Step 1: Preparation of MXene / TPU spinning solution: Weigh 300 mg of monolayer MXene powder and add it to 10 mL of N,N-dimethylformamide (DMF). Ultrasonic treatment is performed at 320 W for 30 min to obtain a uniform monolayer MXene dispersion. Subsequently, 1.0 g of thermoplastic polyurethane elastomer particles is introduced and magnetic stirring is performed at room temperature for 12 h to obtain a binary spinning solution with a MXene content of 30 mg mL -1 MXene / TPU composite wet spinning solution.
[0054] Step 2: Preparation of MXene / TPU fiber: Take the MXene / TPU spinning solution prepared in step 2 for wet spinning. The wet spinning solution is injected into the coagulation bath 1 by the injection pump. Combined with the solvent-coagulation bath double diffusion relationship, continuous wet spinning, spinning fine stream solidification, drawing process and drying are performed to obtain MXene / TPU (M3P) composite wet spinning fibers with controllable fiber diameter. The wet spinning parameters are as follows: the spinning solution flow rate of the syringe is 1.25mL min -1 The needle model is 16G, the collection roller collection speed is 15rpm, the coagulation bath is deionized water, and the average diameter of the fiber is 390μm.
[0055] Example 3: A method for preparing MXene / TPU wet-spun conductive fibers
[0056] Step 1: Preparation of MXene / TPU spinning solution: Weigh 400 mg of monolayer MXene powder and add it to 10 mL N,N-dimethylformamide (DMF). Ultrasonic treatment is performed at 320 W for 30 min to obtain a uniform monolayer MXene dispersion. Subsequently, 1.0 g of thermoplastic polyurethane elastomer particles is introduced and magnetic stirring is performed at room temperature for 12 h to obtain a binary spinning solution with a MXene content of 40 mg mL -1 MXene / TPU composite wet spinning solution.
[0057] Step 2: Preparation of MXene / TPU fiber: Take the MXene / TPU spinning solution prepared in step 2 for wet spinning. The wet spinning solution is injected into the coagulation bath 1 by the injection pump. Combined with the solvent-coagulation bath double diffusion relationship, continuous wet spinning, spinning fine stream solidification, drawing process and drying are performed to obtain MXene / TPU (M4P) composite wet spinning fibers with controllable fiber diameter. The wet spinning parameters are as follows: the spinning solution flow rate of the syringe is 1.25 mL min -1 The needle model is 16G, the collection roller collection speed is 15rpm, the coagulation bath is deionized water, and the average diameter of the fiber is 390μm.
[0058] Example 4: A method for preparing MXene / TPU wet-spun conductive fibers
[0059] Step 1: Preparation of MXene / TPU spinning solution: Weigh 500 mg of monolayer MXene powder and add it to 10 mL of N,N-dimethylformamide (DMF). Ultrasonic treatment is performed at 320 W for 30 min to obtain a uniform monolayer MXene dispersion. Subsequently, 1.0 g of thermoplastic polyurethane elastomer particles is introduced and magnetic stirring is performed at room temperature for 12 h to obtain a binary spinning solution with a MXene content of 50 mg mL -1 MXene / TPU composite wet spinning solution.
[0060] Step 2: Preparation of MXene / TPU fiber: Take the MXene / TPU spinning solution prepared in step 2 for wet spinning. The wet spinning solution is injected into the coagulation bath 1 by the injection pump. Combined with the solvent-coagulation bath double diffusion relationship, continuous wet spinning, spinning fine stream solidification, drawing process and drying are performed to obtain MXene / TPU (M5P) composite wet spinning fibers with controllable fiber diameter. The wet spinning parameters are as follows: the spinning solution flow rate of the syringe is 1.25 mL min -1The needle model is 16G, the collection roller collection speed is 15rpm, the coagulation bath is deionized water, and the average diameter of the fiber is 390μm.
[0061] Example 5: A method for preparing MXene / TPU wet-spun conductive fibers
[0062] Step 1: Preparation of MXene / TPU spinning solution: Weigh 600 mg of monolayer MXene powder and add it to 10 mL N,N-dimethylformamide (DMF). Ultrasonic treatment is performed at 320 W for 30 min to obtain a uniform monolayer MXene dispersion. Subsequently, 1.0 g of thermoplastic polyurethane elastomer particles is introduced and magnetic stirring is performed at room temperature for 12 h to obtain a binary spinning solution with a MXene content of 60 mg mL -1 MXene / TPU composite wet spinning solution.
[0063] Step 2: Preparation of MXene / TPU fiber: Take the MXene / TPU spinning solution prepared in step 2 for wet spinning. The wet spinning solution is injected into the coagulation bath 1 by the injection pump. Combined with the solvent-coagulation bath double diffusion relationship, continuous wet spinning, spinning fine stream solidification, drawing process and drying are performed to obtain MXene / TPU (M6P) composite wet spinning fibers with controllable fiber diameter. The wet spinning parameters are as follows: the spinning solution flow rate of the syringe is 1.25mL min -1 The needle model is 16G, the collection roller collection speed is 15rpm, the coagulation bath is deionized water, and the average diameter of the fiber is 390μm.
[0064] Example 6: Preparation method of PDA@MXene / TPU conductive fiber electrode
[0065] Step 1: Surface functionalization of PDA@MXene: as shown in the attached Figure 1 As shown, Ti3C2T was functionalized by in-situ self-polymerization of dopamine hydrochloride. x MXene system: 0.2 g MXene solid was dispersed in 10 mL deionized water by ultrasonic dispersion, and then 6 mL of 2 mg mL -1 The dopamine hydrochloride solution was reacted at 30°C for 1 hour. The system was centrifuged at 6000 rpm for 10 min to remove unreacted monomers and redispersed in deionized water to obtain surface functionalized PDA@MXene conductive ink.
[0066] Step 2: Examples 1-5 are then dipped into the PDA@MXene conductive ink through the container tank 2, and finally collected by the collecting roller (see the attached device). Figure 1 ) and dried in a vacuum oven at 60 °C to obtain PDA@MXene / TPU (MMx P, X correspond to 2-6) conductive fiber electrodes respectively.
[0067] Example 7: PDA@MXene / TPU smart fabric
[0068] The prepared PDA@MXene / TPU elastic fiber electrode was woven with commercial polytetrafluoroethylene (PTFE) yarn into a plain fabric (8×9 cm 2 ) structure, the excellent triboelectric charge negativity of PTFE yarn and the excellent electrical properties and mechanical flexibility of PDA@MXene / TPU elastic fiber electrodes enable the charge generated by the friction effect of the fabric to be conducted to the external circuit through the PDA@MXene / TPU elastic fiber electrodes. Through repeated contact-separation processes, an AC signal is generated in the external circuit. Through circuit integration, mechanical energy conversion and the driving of small electronic devices can be achieved.
[0069] Self-powered sensor test:
[0070] The plain fabric prepared above is placed on the joints of the human body (elbow joint, knee joint), and the human body movement posture is monitored through the regular changes in the movement amplitude and frequency, such as Fig.15 shown.
[0071] Comparative Example 1:
[0072] MXene / TPU fibers were prepared by referring to the method of Example 1, except that the mass ratio of MXene to TPU was adjusted to 10%, and other conditions were the same as those of Example 1. The conductivity of the prepared fibers was extremely poor and could not be applied in the field of conductive fibers.
[0073] Comparative Example 2:
[0074] MXene / TPU fibers were prepared by referring to the method of Example 1, except that the wet spinning extrusion speed was adjusted to 8 mL min -1 , the drawing rate was 30 rpm, and other conditions were the same as those in Example 1. The prepared fiber did not fully undergo solvent exchange in the coagulation bath, and the fiber structure stability was poor.
[0075] After many tests, it was found that too much MXene addition would result in too low fiber elongation at break, and too little would result in low fiber conductivity. Preferably, the mass ratio of MXene to TPU is 20-60%. In addition, wet spinning conditions are also critical. Adjusting the wet spinning conditions will result in the inability to form fibers. Preferably, the injection speed in the wet spinning process parameters is 1.25 mL / min. -1 , the drawing rate is 15rpm.
[0076] Table 1
[0077]
[0078] The MXene / TPU composite fibers obtained in Examples 1-5 all have stable fiber morphology structures. The conductivity of the composite fibers increases with the increase of the MXene content with excellent electrical properties; at the same time, the tensile properties of the composite fibers decrease with the introduction of MXene. Comparative Example 1 shows that when the MXene addition amount is adjusted to 100 mg, the composite fibers are non-conductive and cannot be used in the field of elastic fiber electrodes. The injection speed and winding speed (1.25 mL / min) of the wet spinning process parameters in Example 3 are adjusted to -1 , 15 rpm) was replaced by 8 mL min -1 and 30 rpm, and other conditions and parameters were consistent with those in Example 3. The obtained fiber failed to achieve full solidification in the coagulation bath, and the fiber molding stability was poor.
[0079] As attached Figure 1 and 2 As shown, PDA@MXene / TPU elastic fiber electrodes can be scalably prepared by continuous wet spinning, drawing and dip coating.
[0080] As attached Figure 3 As shown, the SEM and EDS mapping of the prepared fiber material show that MXene and PDA are evenly distributed on the surface of the PDA@MXene / TPU fiber electrode. Elemental analysis clearly shows the uniform distribution of C, O, and Ti on the fiber surface, confirming the successful combination of PDA@MXene and MXene / TPU wet-spun fibers.
[0081] As attached Figure 4 As shown in the figure, the MXene nanosheets configured in Example 1 have a clear two-dimensional sheet morphology structure, while the functionalized PDA@MXene two-dimensional sheet has an unclear boundary; Figure 5 As shown in the X-ray diffraction (XRD) analysis, it was verified that MXene was successfully prepared and the surface functionalization modification of PDA@MXene did not affect its crystallinity.
[0082] As attached Figure 6 As shown in Figure 3, X-ray photoelectron spectroscopy (XPS) showed that PDA@MXene confirmed the formation of CO-Ti coordination bonds and hydrogen bonds at a binding energy of ~289.4 eV compared to pure MXene. Therefore, the uniform coating of PDA on MXene increases the stability of the structure and electrical properties in humid air.
[0083] As attached Figure 7 As shown in the figure, the MXene / TPU wet-spun conductive fibers have MXene content gradients of 20, 30, 40, 50 and 60 mg mL -1The fiber stress-strain relationship of the dispersed system shows that MXene / TPU wet-spun conductive fibers have excellent mechanical strength and flexibility.
[0084] As attached Figure 8 and 9 As shown, the PDA@MXene / TPU wet-spun conductive fiber electrode has excellent conductivity and good conductivity retention properties.
[0085] As attached Fig.10 It can be seen that the PDA@MXene / TPU-based smart fabric in Example 9 is used for COMSOL potential simulation of the friction nanogenerator.
[0086] Attached Fig.11 , 12 Figures 1 and 13 show the changes in short-circuit current and open-circuit voltage of the PDA@MXene / TPU fabric-based friction nanogenerator in Example 9 with the operating frequency, ambient humidity and contact distance, as well as the cycle stability and output power tests, confirming that the PDA@MXene / TPU fabric-based friction nanogenerator can be stably applied to complex wearable working conditions.
[0087] Attached Fig.14 The PDA@MXene / TPU fabric-based friction nanogenerator in Example 9 is demonstrated to be capable of continuously outputting electrical signals and being used to drive small electronic devices as a power source.
[0088] As attached Fig.15 As shown in the figure, in order to evaluate the potential of PDA@MXene / TPU smart fabrics for human physiological motion monitoring, PDA@MXene / TPU smart fabrics were sewn to the joints of clothing, and the changes in electrical signals accompanying the intensity and amplitude of human motion were recorded. Fig.15 It can be seen that with the increase of the elbow joint movement range, as well as the frequency and intensity of walking and jumping, the output voltage increases significantly. It can be seen that PDA@MXene / TPU smart fabric has excellent human motion monitoring capabilities.
[0089] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing MXene / TPU conductive fiber, characterized in that: The method uses MXene as a conductive material and TPU as an elastic substrate to obtain MXene / TPU conductive fibers through wet spinning; The mass ratio of MXene to TPU is 30-60%; The wet spinning process comprises: Step 1, preparation of MXene / TPU composite solution: using lithium fluoride / hydrochloric acid LiF / HCl mixed solution etching combined with ultrasonic stripping to obtain a MXene colloid aqueous dispersion, dispersing the MXene powder obtained after freeze-drying in N'N-dimethylformamide, adding TPU particles thereto, and magnetically stirring at 25-60°C for 3-48h to obtain a MXene / TPU composite spinning solution; Step 2, preparation of MXene / TPU composite fiber: the above MXene / TPU spinning solution is injected into the coagulation bath by an injection pump, and the spinning fine stream is formed into fiber through a curing process and a drawing process, and the fiber is collected by a coagulation bath collecting device to obtain a MXene / TPU composite fiber.
2. The method according to claim 1, characterized in that The wet spinning conditions are as follows: ultrasonic power of 200-500 W, ultrasonic time of 30-60 min, temperature of 25-60° C., and magnetic stirring time of 3-48 h.
3. The method according to claim 1, characterized in that The coagulation bath of wet spinning is water, and the spinning solution extrusion rate is 1-6 mL min -1 , the drawing rate is 1-30rpm.
4. The MXene / TPU conductive fiber prepared according to the method according to any one of claims 1 to 3.
5. A product containing the MXene / TPU conductive fiber according to claim 4.
6. A PDA@MXene / TPU elastic fiber electrode, characterized in that: The electrode comprises the MXene / TPU conductive fiber and the PDA@MXene coating as described in claim 4, wherein the PDA@MXene refers to a functionalized modified MXene that self-polymerizes dopamine in situ.
7. A smart fabric, characterized in that: The smart fabric comprises the PDA@MXene / TPU elastic fiber electrode and yarn as described in claim 6, and the PDA@MXene / TPU elastic fiber electrode and yarn are interwoven with each other.
8. An application of the PDA@MXene / TPU elastic fiber electrode according to claim 6 in friction nanogenerators, self-powered sensors, wearable electronic devices, smart fibers / fabrics or flexible electrodes.
Citation Information
Patent Citations
High-tensile high-sensitivity piezoresistive fiber as well as preparation method and application thereof
CN112941661A
Cited By
High-modulus MXene-based fiber and preparation method thereof
CN121451329A